2013
DOI: 10.3389/fnint.2013.00097
|View full text |Cite
|
Sign up to set email alerts
|

Stressors impair odor recognition memory via an olfactory bulb-dependent noradrenergic mechanism

Abstract: Non-associative habituation and odor recognition tasks have been widely used to probe questions of social recognition, odor memory duration, and odor memory specificity. Among others, these paradigms have provided valuable insight into how neuromodulation, and specifically norepinephrine/noradrenaline (NE) influences odor memory. In general, NE levels are modulated by arousal, stress, and behavioral state, but there is sparse evidence of a direct relationship between NE and odor memory in adult rodents. The pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
22
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 55 publications
(106 reference statements)
3
22
0
Order By: Relevance
“…A computational model incorporating known cellular and network effects of NE in the OB suggests that NE modulation of OB dynamics are mediating these effects. Interestingly we do not observe acute effects of lacking NE activity during learning, but see significant effects of this temporary manipulation long after the manipulation has stopped, which can underlie observations with respect to NE and stress in the OB (Manella et al, 2013) and NE and integration of adult born neurons into the network (Moreno et al, 2012).…”
Section: Resultssupporting
confidence: 51%
“…A computational model incorporating known cellular and network effects of NE in the OB suggests that NE modulation of OB dynamics are mediating these effects. Interestingly we do not observe acute effects of lacking NE activity during learning, but see significant effects of this temporary manipulation long after the manipulation has stopped, which can underlie observations with respect to NE and stress in the OB (Manella et al, 2013) and NE and integration of adult born neurons into the network (Moreno et al, 2012).…”
Section: Resultssupporting
confidence: 51%
“…Initial physiological studies of these neurons had indicated that they were glutamatergic and excitatory (Aungst et al, 2003); however, subsequent studies demonstrated that they are GABAergic and dopaminergic (Liu et al, 2013), and indeed probably constitute one extreme of a single morphologically heterogeneous class of interneurons that includes periglomerular cells (Kiyokage et al, 2010;McGann, 2013;Sethupathy et al, 2013). This is interesting because recent work has shown that, despite their GABAergic phenotype, sSA cells are clearly the effectors of a functionally excitatory lateral network that results in the broad and graded inhibition of mitral cells (Marbach and Albeanu, 2011). This lateral excitatory effect across the sSA network potentially could arise via gap-junction coupling among sSA and periglomerular cells, or by rendering GABAergic synapses onto periglomerular and sSA cells excitatory owing to a reversed chloride gradient in these neurons.…”
Section: Feedback Normalizationmentioning
confidence: 99%
“…These mechanisms lead to sensory filtering and habituation of perception. Manella et al ( 2013 ) studied how the modulatory norepinephrine system in the brain influences odor habituation and odor memory in rats.…”
mentioning
confidence: 99%